2013
DOI: 10.1177/0898264313488164
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Caregiving and Health Dynamics of Caregivers for People With AIDS

Abstract: Objectives: A cohort of older people living in a low-resource setting in Nairobi is followed to understand the transitions in caregiving status and trajectories in health over a three-year period.Methods: Three categories of older people comprising 65 AIDS caregivers, 102 Other caregivers and 1,322 non-caregivers identified at baseline were assessed at end-line based on two self-reported health outcome measures, a functionality score and having a severe health problem.Results: A majority of caregivers were sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Furthermore, research has also established that caregiving can endanger the health of caregivers (Chepngeno-Langat & Evandrou, 2013), place emotional strain on household members (Steinberg, Johnson, Schierhout, & Ndegwa, 2002), and result in loss of income and increased care-related expenses which can push affected households deeper into poverty (Collins & Leibbrandt, 2007).…”
mentioning
confidence: 99%
“…Furthermore, research has also established that caregiving can endanger the health of caregivers (Chepngeno-Langat & Evandrou, 2013), place emotional strain on household members (Steinberg, Johnson, Schierhout, & Ndegwa, 2002), and result in loss of income and increased care-related expenses which can push affected households deeper into poverty (Collins & Leibbrandt, 2007).…”
mentioning
confidence: 99%
“…In a similar vein, the notion of disparities in older men and women's health and physical capacity with women at a clear disadvantage, concurs with a body of robust evidence, showing similar gender inequalities in health status and health-related quality of life in old age in various Sub Saharan African settings [41][42][43][44][45][46][47][48][49]. The common perception, that older women's poorer health is due, in part, to the physical strain associated with their domestic and care roles, chimes broadly with research evidence from SSA on the negative impacts of older persons' caregiving roles on their physical and mental well-being, particularly in contexts of HIV/AIDS [50][51][52][53][54]. These results are in line with a study by [55], who analyzed the situation of the elderly in Ghana, and concluded that elderly females are more vulnerable and disadvantaged than their male counterparts due to low educational attainment resulting in low female participation in the formal sector.…”
Section: Discussionmentioning
confidence: 99%
“…The first is serial caregiving-many OAs care for one adult child, and then another-either concurrently or sequentially, as well as their offspring. In Kenya, 10% of noncaregiving OAs in a household transitioned into caregiving and 50% of these caregivers were providing care transitioned to noncaregiving status (Chepngeno-Langat & Evandrou, 2013). A second feature is the number of carerecipients, which are generally not analyzed with regard to caregiver health outcomes or asset dissolution.…”
Section: Health Impactsmentioning
confidence: 99%